Structure formation and peculiarities of crystallisation of lead-free tin – zinc alloys obtained by rapid solidification - Zernitsa, Denis A.; Shepelevich, Vasili G. (Journal of the Belarusian State University. Physics, 2022)
The results of the study of the microstructure of lead-free alloys of the tin – zinc system obtained by rapid solidification at a cooling rate of at least 105 K/s are presented. In tin and zinc alloys with concentrations of 1.2–2.0 wt. % Zn and 1.5 wt. % Sn, respectively, during rapidly cooling of the melt, the alloying element is captured. The formed solid solutions are supersaturated and at room temperature disintegrate according to the mechanism of formation and growth of nuclei of a new phase. The average size of zinc and tin precipitates after holding the foil for two days does not exceed 0.5 μm. Melts of compositions Sn – 4.4–15.0 wt. % Zn after rapidly cooling are supercooled and supersaturated by two components and experience spinodal decomposition (stratification) followed by the formation of supersaturated solid solutions based on tin and zinc, which disintegrate at room temperature. The average size of zinc precipitates in non-equilibrium eutectic does not exceed 2 μm. In rapid solidificated foils of alloys containing 50–80 wt. % Zn, a two-phase structure is formed from solid solutions based on tin and zinc. The average size of tin precipitates does not exceed 1 μm. As the crystallisation front moves away from the contact surface of the foil with the surface of the mold, the tin particles become larger and the specific surface of the interphase boundary decreases.